Preoperative plasticity in the functional naming network of patients with left insular gliomas - Elisa Cargnelutti; Marta Maieron; Serena D'Agostini; Tamara Ius; Miran Skrap; Barbara Tomasino (NeuroImage: Clinical, 2024)
Plasticity could take place as a compensatory process following brain glioma growth. Only a few studies specifically explored plasticity in patients affected by a glioma invading the left insula; even more, plasticity of the insular cortex in task-based functional language network is almost unexplored.In the current study, we explored potential plasticity in a consecutive series of 22 patients affected by a glioma centered to the left insula, by comparing their preoperative object-naming functional network with that of a group of healthy controls. After having controlled for demographic variables, fMRI results showed that patients vs. controls activated a cluster in the right, contralesional pars triangularis including the Broca’s area. On the other hand, controls did not significantly activate any brain region more than patients. At behavioral level, patients retained a generally preserved naming performance as well as a proficient language processing profile.These findings suggest that involvement of language-specific areas in the healthy hemisphere could help compensate for the left, affected insula, thus allowing preservation of the naming functions. Results are commented in relation to lesion site, naming performance, and potential relevance for neurosurgery.